2017
DOI: 10.3390/diagnostics7030050
|View full text |Cite
|
Sign up to set email alerts
|

Using Naïve Bayesian Analysis to Determine Imaging Characteristics of KRAS Mutations in Metastatic Colon Cancer

Abstract: Genotype, particularly Ras status, greatly affects prognosis and treatment of liver metastasis in colon cancer patients. This pilot aimed to apply word frequency analysis and a naive Bayes classifier on radiology reports to extract distinguishing imaging descriptors of wild-type colon cancer patients and those with v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) mutations. In this institutional-review-board-approved study, we compiled a SNaPshot mutation analysis dataset from 457 colon adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…By comparing the mutation rates of KRAS in different countries (Table 3), the following conclusions were drawn: the KRAS mutation rate among Americans is the highest [15][16][17][18][19], followed by Europeans [33][34][35][36][37][38][39][40][41][42], and then Asians [20][21][22][23][24][25][26][27][28][29][30][31][32]. KRAS is the most important member of the RAS family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the mutation rates of KRAS in different countries (Table 3), the following conclusions were drawn: the KRAS mutation rate among Americans is the highest [15][16][17][18][19], followed by Europeans [33][34][35][36][37][38][39][40][41][42], and then Asians [20][21][22][23][24][25][26][27][28][29][30][31][32]. KRAS is the most important member of the RAS family.…”
Section: Discussionmentioning
confidence: 99%
“…In Western European countries [33][34][35][36][37][38][39][40][43][44], most studies demonstrated that the RAF mutation rate was over 10%. In the United States, only a few studies demonstrated a higher mutation rate of RAF [15][16][17]45]. In Asia, the mutation rate is the lowest, ranging between 4-9% [24][25][26][27][28][45][46][47].…”
Section: : Ras Raf and Msi Status Of Colorectal Cancermentioning
confidence: 99%
“…NLP for the analysis of radiology reports has also been explored in the context of other cancer types, including hepatocellular carcinomas, [13][14][15][16] breast cancer, [17][18][19][20] lung cancer, [21][22][23] and other abdominal or pelvic tumors. 11,[24][25][26][27] All studies that provided sufficient insight into their modeling approach used a bag-of-words approach. To our knowledge, this study presents the first sequence-based NLP approach for analyzing free-text radiology reports in oncology patients as well as the first head-to-head comparison of sequence-based and bag-of-words models for medical text analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the domain of image analysis, Pershad et al used a purely text-based approach to process the descriptive words used by radiologists in their reports in order to predict KRAS mutational status [178]. The trained classifier determined the word frequency within both mutant and wildtype radiology report.…”
Section: Colorectal Carcinomamentioning
confidence: 99%